Bioequivalence of Two Oral Formulations of Moxifloxacin and Its Analytical Study by Hplc-Uv Method - M.Sher (Pakistan Journal of Science, 2010)
An HPLC-UV method was developed which permits determination, bioequivalence and stability of moxifloxacin in tablets. The chromatographic separation was achieved on C18 column in isocratic mode (methanol, water and acetonitrile 45:30:25) at pH 4 and eluents were detected at 295nm. After single oral dose (400 mg) of two formulations (Avelox, Bayer and Staxin, Stand Pharma) of moxifloxacin administered to healthy volunteers, pharmacokinetics parameters were derived from the plasma concentrations curves for both formulations. Both of the formulations were bioequivalent on the basis of pharmacokinetic analysis with no adverse reactions of drug were observed. The present method is effective extraction technique with good reproducible recovery and a limit of quantification of 20 ng.ml-1. The method was successfully applied for stability studies of moxifloxacin tablets for six months and has been found stable at accelerated conditions of temperature and relative humidity.